Avian Diversity on the Sandstone Cliff Outskirts of the Maloti/Drakensberg ‘Hot-spot’ Area in Southern Africa - Kopij, G. (Вестник зоологии, 2013)
During the year 1999-2001, avian assemblages associated with cliffs and bushy vegetation of the Clarens Formation have been quantified by means of the line transect method (total length of transects — 107 km) in Lesotho lowlands. In total, 80 species resident in these habitats were recorded. Overall, six species were classified as dominants: Serinus canicollis, Prinia maculosa, Streptopelia senegalensis, Emberiza tahapisi, Emberiza capensis and Cisticola fulvicapilla. Together they comprised 41.4?% of all breeding pairs. Ten other species were classified as subdominants (33.9?%). Granivores were the most numerous feeding guild (31 species; 48.0?% of all pairs), followed by insectivores (27 species; 32.3?%) and frugivores (11 species; 17.4?%). The most numerous nesting guild were shrub/tree nesting birds (47.2?%). Proportions for some congereric species were calculated. The bushy vegetation is characterized by high species diversity and relatively high population densities of some species.